Generasi Unggul Berkarakter dengan Soft Skill Enterpreneur Mewujudkan Pembangunan Berkelanjutan Siswa SMK Bina Mitra - Sri Winda Hardiyanti Daminik; Jon Edy; Suryana Suryana; Siva Marsya Oktaviany; Dini Maelani; Salsabila Sayyidina (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Sustainable development requires a superior generation that not only has technical knowledge, but also soft skills to face increasingly complex global challenges. Soft skills include abilities such as communication, leadership, teamwork, problem solving, creativity, and work ethics, which are very important in supporting the achievement of the Sustainable Development Goals. A superior generation with good mastery of soft skills is able to become innovative and competitive agents of change, while contributing to creating social, economic and environmental balance. This research highlights the importance of integrating soft skills development in education and training systems, both formal and non-formal, as a strategy to build the capacity of the younger generation. A holistic approach is needed, involving collaboration between the government, educational institutions, community organizations and the private sector in creating a learning environment that supports the strengthening of soft skills. Through experiential learning, leadership training, and character development programs, young people can develop their potential in line with the needs of the world of work and the demands of sustainability. Research results show that generations who excel in soft skills have a greater ability to adapt to change, work in cross-cultural teams, and create innovative solutions to problems